Analisis Postur Kerja Anak Sekolah Dasar Saat Menggunakan Komputer: Sebuah Studi Kasus - Martika Mayangsari; Irwan Iftadi; Taufiq Rochman (Performa: Media Ilmiah Teknik Industri, 2013)
In several countries including Indonesia, compters used increas every year. Computer use is notonly by adults or office but also children and primary school had been using the computer. Increasing computer used in children couse problems pain and stiffnessin the arms, neck, shoulders and around the back after using the computer. In this study to evaluate children working posture using computer. Assessment of children working posture performed on SDN 15 dan SD Widya WAcana 2 Surakarta using Rapid Upper Limb Assessment (RULA). RULA evaluation of children who have no score boxes at both schools.